Utilizing Date Seed Waste Meal as an Alternative Feed for Pullets - Ali Omar Altwoate; Abdulruhman B. Alnakaa; Mahmoud Ahmed Abomhara; Mohamed Omar Altaib (African Journal of Advanced Pure and Applied Sciences, 2024)
The study aimed to investigate the impact of incorporating varying levels of date seed waste meal (DSWM) in the diet of pullets (local strain chicks) aged 1-16 weeks. Three levels of DSWM (0.0, 100 kg, and 200 kg) were tested in the pullets’ diets. Additionally, there were five sub-treatments for the 100 kg and 200 kg DSWM levels, including a negative control group, phytase, Optizyme, amino acid supplementation, and crumble diet formulation. The study evaluated productive performance, carcass characteristics, chemical composition of carcass, and economic efficiency. Results showed that adding amino acids or pelleting diets with 100 kg or 200 kg DSWM improved growth performance from 1-4 weeks of age. Optizyme addition resulted in the best overall productive traits. Feed intake decreased linearly with increasing DSWM levels, but enzyme or amino acid supplementation and crumble treatments did not significantly affect feed consumption. The inclusion of 100 kg or 200 kg DSWM improved feed conversion ratio (FCR) compared to the control, with no significant interaction between DSWM level and dietary treatments. DSWM up to 200 kg did not negatively impact pullet mortality. Carcass characteristics, body organs, and meat composition were not adversely affected by DSWM level, feed additives, or crumble treatments. Economic efficiency analysis suggested that pullets aged 1-16 weeks could be fed diets containing 200 kg DSWM when supplemented with phytase, Optizyme, amino acids, and a crumble diet formulation. In conclusion, incorporating up to 200 kg of date seed waste meal in the diets of slow-growing pullets did not affect productive performance. The best feed conversion and economic efficiency were observed in pullets-fed diets containing 200 kg DSWM supplemented with various treatments.